INTERCULTURAL COMMUNICATION AT HIGHER EDUCATION CONTEXT: PORTRAITS AND PRACTICES - Wello, Muh. Basri; Nur, Sahril; Azis, Astuti (International Journal of Language Education, 2017)
Intercultural communication focuses on the importance of understanding otherâ€™s language and cultural background in order to create appropriate and effective communication. This article reviews several studies on intercultural competence from five different countries. The objective of this review is to present research from different context, models of intercultural communication developed in those settings and posÂsible adaptive models to develop in Indonesian higher educational settings. Data were obtained from a careful review of international articles on the study of intercultural communication using inclusion and exclusion criÂteria. Result of the review reveals that culture is still the biggest issue that could block effective and relevant communication. For that reason, intercultural communication, (IC) positively contribute to the development of cultural sensitivity and is open for adaptation to work in different context. Suggestions on effective model of intercultural education at university level and applicable sample of collegial relationship among academics are also provided.